Towards a cropping system sustainability tool (CROSST) - Pilot results from evaluating green manure cover crops in Benin and Kenya - Mukiri, Jessica; Diogo, Rodrigue V. Cao; Gbedjissokpa, Sènami G.M.; Kinyua, Michael; Hoek, Rein van der; Sommer, Rolf; Paul, Birthe K. (International Center for Tropical Agriculture, 2019)
Farming practices in sub-Saharan Africa have resulted in declining soil fertility. Hence, Green Manure Cover Crops (GMCC) are promoted for soil improvement and protection. Adoption of GMCCs by farmers, including integration in their cropping systems, requires a good understanding of the multi-dimensional impacts of these crops. We, therefore, developed the Cropping Systems Assessment Sustainability Tool (CROSST), which can compare the performance of different cropping systems with and without the integration of GMCCs. CROSST is an Excel-based tool that assesses both agro-environmental and socio-economic impacts of GMCC technologies. The tool quantifies gross economic margin, productivity (yield), soil health (N and P balances, soil structure, and soil organic carbon), required labour hours, and the trade-offs between these indicators. The tool was pilot-tested in Benin and Kenya under the BMZ-GIZ program on ‘Soil Protection and Rehabilitation for Food Security.’ Data was collected through literature reviews, focus group discussions and key expert interviews. The compared cropping systems were selected and designed by experts with in-depth knowledge on local contexts of Benin and Western Kenya. The first results indicate that GMCCs improve soil structure/soil organic matter as well as soil N balances in both countries. However, investing in soil improvement can result in loss of profitability, especially when a crop that produces grain for consumption or sale is swapped for a GMCC that produces biomass for soil amendment only. CROSST still needs further data refinement with recent official census as well as independent field measurements. Once validated, it can serve as a decision-support tool for development agencies, implementing partners, and local stakeholders when designing sustainable cropping systems that integrate GMCCs.